Lung Function Impairment Among Firefighter After Forest Fire Disaster in Riau, Sumatra - Rudi Kurniawan; Seira Putri Boru Rambe; Indra Yovie; Erlang Samoedro; Agus Dwi Susanto; Jamal Zaini (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: The 2015 forest fire disaster affected almost 2.6 million hectares of land in Indonesia, and Riau was among the worst. Firefighters were the first responders to deal with the disaster, but a little was known about the influence of extinguishing forest fire activities with their health. This study aimed to evaluate respiratory symptoms and lung function among firefighters 6 months after forest fire exposure.Methods: Interviews were conducted regarding sociodemographic factors, respiratory symptoms, and history of forest fire exposure during the disaster. Spirometry and chest X-ray were also carried out with standard techniques. Statistical analysis was performed based on the existing data. Ninety firefighters participated in this study, most were male with mean age of 33 years old. About 66% were smoker, had been working as firefighters for 2 to 10 years, and had been on extinguishing forest fire duty around 2–5 hours/day during the disaster.Results: All firefighters reported respiratory symptoms after 3 months. Pulmonary function was abnormal in 50% of subjects with mild restrictive characteristic. The analysis showed that body mass index (BMI) and duration of exposure had a significant correlation with pulmonary function abnormality.Conclusion: Pulmonary function was found abnormal in most subjects 6 months after forest fire exposure in Riau.